How Does Democracy Cause Growth? - Vanessa A. Boese-Schlosser; Markus Eberhardt (Wissenschaftszentrum Berlin für Sozialforschung (WZB), 2023)
Recent empirical work has established that 'democracy causes growth'. In this paper, we determine the underlying institutions which drive this relationship using data from the Varieties of Democracy project. We sketch how incentives and opportunities as well as the distribution of political power shaped by underlying institutions, in combination with the extent of the market, endogenously form an 'economic blueprint for growth', which likely differs across countries. We take our model to the data by adopting novel heterogeneous treatment effects estimators, which allow for non-parallel trends and selection into institutional change, and run horse races between underlying institutions. We find that freedom of expression, clean elections, and legislative executive constraints are the foremost drivers of long-run development. Erosion of these institutions, as witnessed recently in many countries, may jeopardise the perpetual growth effect of becoming a liberal democracy we establish for the post-WWII period.
Keywords: O10; P16; C23; 320; Democracy; Growth; Institutions; Interactive Fixed Effects; Difference-in-Difference